MENINGKATKAN EFEKTIFITAS BELAJAR MATEMATIKA PADA MATERI LOGARITMA MELALUI STRATEGI PEMBELAJARAN AKTIF SISWA KELAS X MIPA-5 SMA NEGERI 1 SIGLI - Eva Defiana (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
The purpose of this study was to increase the effectiveness of learning mathematics on logarithmic material. The benefit of this research is to improve the mastery of logarithmic material through active learning strategies. The subjects of this classroom action research are students of class X MIPA-5 SMA Negeri 1 Sigli while the object is learning logarithmic material in Mathematics which is taught by activating students in small groups and large groups. From the research conducted by examining the initial conditions of students as measured by written test instruments and the results of classroom action research with 2 cycles, it is seen that there is an increase in the results achieved by students in mastering the given logarithmic material. The increase in the average value is 62.85 in the pre-cycle to 68.42 in the first cycle and becomes 77.2 in the second cycle. The percentage of completeness from 57.15% in the initial conditions to 68.58% in the first cycle and increased in the second cycle to 94.29%.Keywords: Active Learning, Effective Learning, and Logarithm